Gaya Belajar Visual, Auditori, Kinestetik terhadap Hasil Belajar Siswa - Deisye Supit; Melianti Melianti; Elizabeth Meiske Maythy Lasut; Noldin Jerry Tumbel (Journal on Education, 2023)
This quantitative research which is descriptive and correlation in nature aims to examine the relationship of learning styles to the results of student academic achievement. The population in this study were students of SMP X Airmadidi. The sampling technique used is the convenience sampling method. The number of respondents in this study were 93 students. The instruments used in this study were a questionnaire adapted from Maramis (2012) and the average student scores listed in the report cards for Semester 1. Academic Year 2020-2021. The data analysis technique used to determine the level of student learning styles and the level of student academic achievement is the Mean score and Correlation to determine the relationship between learning style and academic achievement. The results showed that the three learning styles possessed by students were in the high category and the level of student achievement in very good category. Furthermore, the results of this study indicate that there is no significant relationship between visual, auditory and kinesthetic learning styles. It is recommended that teachers should pay attention to learning styles using practice, especially using visual aids when teaching in class.